Bone marrow mesenchymal stem cells protect alveolar macrophages from lipopolysaccharide‐induced apoptosis partially by inhibiting the Wnt/β‐catenin pathway. (17th September 2014) - Li, Bin; Zhang, Hongwu; Zeng, Mian; He, Wanmei; Li, Ming; Huang, Xubin; Deng, David Y. B.; Wu, Jianfeng
Abstract Apoptosis of alveolar macrophages (AMs) plays a pathogenic role in acute lung injury (ALI) and its severe type, acute respiratory distress syndrome (ARDS). Mesenchymal stem cells (MSCs) are promising therapeutic cells for preventing apoptosis and eliminating cellular injury. We investigated the effects of rat bone marrow mesenchymal stem cells (BMSCs) on lipopolysaccharide (LPS)‐induced apoptosis in AMs using transwell experiments, and examined the underlying mechanisms LPS induced AMs apoptosis in a dose‐ and time‐dependent fashion, whereas BMSCs reduced AMs apoptosis when co‐cultured at appropriate ratios. BMSCs decreased expression of cleaved caspase‐3 and the pro‐apoptotic protein, Bax, whilst increased levels of the anti‐apoptotic protein, Bcl‐2, prolonging the lifespan of AMs in vitro. Promotion of AMs survival by BMSCs required down‐regulation of p‐GSK‐3β and β‐catenin in AMs. The anti‐apoptosis action of BMSCs was reversed by SB216763, a specific inhibitor of GSK‐3β that also activates Wnt/β‐catenin signaling. In conclusion, BMSCs can attenuate AM apoptosis partially by suppressing the Wnt/β‐catenin pathway.